Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4103/0971-5916.184289
|View full text |Cite
|
Sign up to set email alerts
|

Prescription pattern of antidepressants in five tertiary care psychiatric centres of India

Abstract: Background & objectives:Limited data are available on prescription patterns of the antidepressants from India. We studied antidepressants’ prescription pattern from five geographically distant tertiary psychiatric care centers of the India.Method:In this cross-sectional study, all patients who attended outpatients department or were admitted in the psychiatry wards at Lucknow, Chandigarh, Tiruvalla, Mumbai and Guwahati on a fixed day, who were using or had been prescribed antidepressant medications, were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 17 publications
5
21
0
3
Order By: Relevance
“…Total of 56 study subjects having co-morbidities along with depression were included this study. Most of the subjects (26.79%) were found to have hypertension, followed by 25% subjects with diabetes mellitus which is similar to the study conducted by Adarsh Tripathi et al, where most of the subjects (5.78%) were found to have Diabetes Mellitus (Tripathi et al, 2016).…”
Section: Distribution Of Subjects Based On Medication Adherencesupporting
confidence: 87%
“…Total of 56 study subjects having co-morbidities along with depression were included this study. Most of the subjects (26.79%) were found to have hypertension, followed by 25% subjects with diabetes mellitus which is similar to the study conducted by Adarsh Tripathi et al, where most of the subjects (5.78%) were found to have Diabetes Mellitus (Tripathi et al, 2016).…”
Section: Distribution Of Subjects Based On Medication Adherencesupporting
confidence: 87%
“…Overall, 272 (87.18%) patients were using newer antidepressants. 13 Boulenger JP et al compared efficacy of long-term treatment with escitalopram and paroxetine in severely depressed patients and found that escitalopram as significantly more effective than paroxetine in the long-term treatment of severely depressed patients. 14 The above studies indicate that use of SSRIs is much more common in comparison to other group of antidepressant drug for the management of depression and other psychotic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This survey showed that SGA’s are the main antipsychotic drugs for the treatment of Schizophrenia in Asia 3. Another survey on the use of antidepressants was conducted in 2014 by East Asia and South Asia 4,5…”
Section: Introductionmentioning
confidence: 97%